The Ethical Costs of Artificial Intelligence: Investigating How and When Workplace Artificial Intelligence Usage Promotes Employee Unethical Outcomes - Zhao, Puchu (Journal of business ethics, 2026)
The use of artificial intelligence (AI) among employees has become a prevalent phenomenon in workplaces today. Existing research has universally illustrated that employees’ AI usage is a positive practice yielding numerous benefits, such as enhanced performance and productivity. However, we challenge this consensus by exploring the ethical costs of employees’ AI usage. Drawing on theories of moral relativism, we suggest that employees’ AI usage triggers their metaethical belief of moral relativism, which in turn not only induces workplace deviance within themselves but also leads to their lenient moral judgment toward others. Furthermore, we propose that these effects are especially pronounced among employees low in moral identity. We found empirical support through two experiments and a three-wave longitudinal survey among Chinese and US employees. Overall, the present research not only advances knowledge on the dark side of employees’ AI usage but also makes substantial contributions to behavioral ethics and moral psychology in the AI era.